Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1143/jjap.49.061001
|View full text |Cite
|
Sign up to set email alerts
|

High-Mobility AlGaN/GaN Two-Dimensional Electron Gas Heterostructure Grown on (111) Single Crystal Diamond Substrate

Abstract: High mobility Al0.28Ga0.72N/GaN two-dimensional electron gas (2DEG) is achieved on (111) oriented single crystal diamond substrate. The surface morphology of the epilayer is free of cracks thanks to the use of an AlN interlayer for strain relaxation. The rms roughness of the sample surface deduced from atomic force microscopy is 0.6 nm for a 2 ×2 µm2 scan area, which indicates an excellent surface morphology. Hall effect measurements reveal a 2DEG with room temperature mobility and sheet carrier density of 750… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The thermal mismatch with different TECs also induces a high tensile strain in the epilayer during the cooling down of the sample after growth. There are a lot of efforts in the GaN deposited on different types of diamond substrates, such as single crystal diamond (SCD) with (110), (111) or (100) orientations, nano-crystalline diamond, polycrystalline diamond, or the highly misoriented diamond substrate [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. The growth methods include metal organic chemical vapor deposition (MOCVD), molecular beam epitaxial (MBE), HVPE and resonance plasma enhanced MOCVD (ECR-MOCVD) [49][50][51][52][53][54][55][56][57][58][59].…”
Section: Gan Epitaxially Grown On the Diamond Substratementioning
confidence: 99%
“…The thermal mismatch with different TECs also induces a high tensile strain in the epilayer during the cooling down of the sample after growth. There are a lot of efforts in the GaN deposited on different types of diamond substrates, such as single crystal diamond (SCD) with (110), (111) or (100) orientations, nano-crystalline diamond, polycrystalline diamond, or the highly misoriented diamond substrate [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. The growth methods include metal organic chemical vapor deposition (MOCVD), molecular beam epitaxial (MBE), HVPE and resonance plasma enhanced MOCVD (ECR-MOCVD) [49][50][51][52][53][54][55][56][57][58][59].…”
Section: Gan Epitaxially Grown On the Diamond Substratementioning
confidence: 99%
“…They subsequently used this single-crystal AlN as a buffer layer to deposit epitaxially AlGaN/GaN HEMTs on diamond, and successfully demonstrated high-power RF operation at 1 GHz with a significant reduction in deviceoperation temperature [14,15,16,17]. Similarly, a European group deposited epitaxial AlGaN/GaN HEMT structures on (111) diamond using molecular beam epitaxy [18,19]. The HEMTs exhibited outstanding RF performance anda cut-off frequency of 21 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…11 Very recently, Alomari et al reported the dc and small-signal rf characteristics of AlGaN/GaN HEMTs grown on diamond ͑111͒ substrates by molecular beam epitaxy. 12,13 In this study, using MOVPE, we epitaxially grew a single-crystal AlGaN/GaN heterostructure on a diamond ͑111͒ substrate. Next, we confirmed two-dimensional electron gas ͑2DEG͒.We then measured the dc, rf and thermal characteristics.…”
mentioning
confidence: 99%